Motivasi, Pengetahuan CPA, Big Five Personality, dan Minat Mahasiswa Berkarier sebagai Akuntan Publik - Rahayu, Kharisma Milinia Muji; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 33 No 11 (2023)DO - 10.24843/EJA.2023.v33.i11.p09, 2023)
The purpose of this research is to test empirically student interest in a career as a public accountant in terms of self-motivation, knowledge of Certified Public Accountants, and big five personality which include extraversion, agreeableness, conscientiousness, emotional stability, and openness to experience. The research was conducted on 2019 and 2020 students of the Accounting Undergraduate Study Program of the Faculty of Economics and Business, Udayana University. Data was collected through the survey method by distributing questionnaires. Samples were taken using simple random sampling method obtained by 250 respondents. The analysis technique used is Partial Least Square (PLS). The results showed that self-motivation, knowledge of Certified Public Accountants, conscientiousness personality type, emotional stability personality type, and openness to experience personality type had a positive effect on student interest in a career as a public accountant, while extraversion personality type and agreeableness personality type had no effect on student interest in a career as a public accountant. Kelywords: Sellf Motivation; Knowleldgel of CPAs; Big Fivel Pelrsonality; Intelrelst; Public Accountant